2023
DOI: 10.1021/acs.estlett.3c00185
|View full text |Cite
|
Sign up to set email alerts
|

Sucralose and Predicted De Facto Wastewater Reuse Levels Correlate with PFAS Levels in Surface Waters

Abstract: Per-and polyfluoroalkyl substances (PFAS) pose risks to human health and ecosystems and are commonly found in wastewater treatment plant (WWTP) effluents discharged into surface waters. WWTPs continuously discharging PFAS into surface waters are hypothesized to lead to pervasive PFAS for downstream drinking water treatment plant (DWTP) intakes. To investigate the impact of this unplanned (de facto) wastewater reuse, we analyzed river water and WWTP effluent samples for 19 target PFAS and a surrogate chemical (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Here, we attempted to use this relationship to reveal the source of PFAS contamination. However, in Islam et al, the sucralose concentration was >100 times higher than the PFAS concentration. In our case, we found much higher ∑PFAS concentrations (up to 18,000 ng L –1 ) and lower sucralose concentrations (up to 7000 ng L –1 ).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Here, we attempted to use this relationship to reveal the source of PFAS contamination. However, in Islam et al, the sucralose concentration was >100 times higher than the PFAS concentration. In our case, we found much higher ∑PFAS concentrations (up to 18,000 ng L –1 ) and lower sucralose concentrations (up to 7000 ng L –1 ).…”
Section: Resultsmentioning
confidence: 85%
“…Islam et al showed a direct and linear relationship between ∑PFAS and sucralose concentrations to predict de facto water reuse. Here, we attempted to use this relationship to reveal the source of PFAS contamination.…”
Section: Resultsmentioning
confidence: 99%